Studi Eksplorasi Program Edunation dalam Mempersiapkan Fasilitator Belajar di Yayasan Emmanuel - Yubali Ani; Ashiong Parhehean Munthe; Widiastuti Widiastuti (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2019)
The Edunation Program at Emmanuel Foundation is a program that prepares the learning facilitators (instructors) who are sitting at the high school level to be able to teach elementary students in the surrounding environment. The purpose of this study was to explore: (1) the activities that needed to prepare learning facilitators at Emmanuel Foundation; (2) the implementation of the Edunation program in preparing this learning facilitator; (3) material provided in preparing learning facilitators; (4) benefits obtained by learning facilitators, Emmanuel Foundation, and students taught through this program; and (5) obstacles faced in implementing the Edu-nation program in preparing facilitators. The research method was descriptive qualitative research exploration methods. Research subject was 20 students. The research was conducted from March-June 2018. Data collection techniques were interviews and observation. The results of this research included: 1) training, direct practice, visited to the place of teaching facilitators, making teaching aids, varied games; 2) there were eight time sessions for one semester; 3) the material provided was pedagogy, basic content (read-write-calculate), class management, and self-recognition; 4) learning facilitators became more concerned with school-age students in their environment, Emmanuel Foundation achieved the expected vision of each student, and students become more enthusiastic in learning; 5) the constraints faced were the time involved with school activities from one of the participating schools.